Islamic Republic of Afghanistan Agricultural Sector Review : Revitalizing Agriculture for Economic Growth, Job Creation and Food Security - World Bank (Washington, DC, 2015)
Economic growth, job creation, and development are central to the decade of transformation (2015-25) and long-term security for the people of Afghanistan. The Bank and the Government of the Islamic Republic of Afghanistan (GoIRA) recognize that agriculture and rural development are a key to inclusive growth, and hence need renewed vigor and strategic long-term investments. Further, the Bank and the GoIRA acknowledge that increases in agricultural productivity and market access for smallholders are critical for rural development, job creation, and food security in Afghanistan. Sections two and three of this report describe the agricultural sector and its current and potential roles in the Afghan economy, and present the rationale for choosing certain areas and subsectors for a selective 'first mover' strategy to achieve early gains. Section four outlines the constraints and potential in each of the three value chains proposed for the selective strategy, irrigated wheat, intensive livestock production, and horticulture. Section five describes cross-cutting constraints and how best to address them, and Section six proposes measures to help the rural poor who will not benefit much from the first-mover strategy. Section seven summarizes the recommendations of the review and their expected results for jobs and incomes.